Effect of Music Therapy on Sleep, Stress, and Anxiety Level in Patients Undergoing Overnight Polysomnography: A Randomized-Controlled Trial - Suwansathit, Worakot; Tantrakul, Visasiri; Pengjam, Janejira; Amornputthisathaporn, Naparat (Ramathibodi Medical Journal, 2018)
Background: Music therapy has been used in various types of clinical settings to improve sleep quality and reduce stress and anxiety. Objective: To determine the effect of music therapy on sleep and stress level in subjects who undergo standard overnight polysomnography (PSG). Methods: A randomized-controlled trial was conducted at Ramathibodi Hospital Sleep Center. One hundred forty subjects scheduled for standard overnight PSG for the first time were enrolled (70 subjects each in music and control groups). While the control group received only standard care, 30-minute of Thai light music was given to the experimental group during hook up time prior to initiation of PSG. Results: Compared to controls, stress, and anxiety level after PSG in the music group were significantly lower reflected in post-intervention State Trait questionnaire (35.6 ± 10.8 vs 47.6 ± 6.1; P < 0.01) and difference of pre- and post- PSG State Trait score (-12.4 ± 12.8 vs 0.52 ± 7.7; P < 0.01). Conclusions: Music therapy substantially reduced stress and anxiety related with overnight PSG. Thus, these could be offered to patients prior to initiation of the sleep test for relaxation. However, there was no alteration in sleep architecture and other sleep quality indices associated with music therapy.